Regional Economic Forecasting: State-of-the-Art Methodology and Future Challenge - Robert Lehmann; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2014)
Over the last decade, the topic of regional economic forecasting has become increasingly prevalent in academic literature. The most striking problem in this context is data availability at a regional level. However, considerable methodological improvements have been made to address this problem. This paper summarizes a multitude of articles from academic journals and describes state-of-the-art techniques in regional economic forecasting. After identifying current practices, the article closes with a roadmap for possible future research activities.
Keywords: E27; E37; 330; regional economic forecasting; regional gross-domestic product; regional labour markets